Wind turbine proximity and health: Longitudinal evidence from US households - Niklas Rott; Douglas Almond; Osea Giuntella (Proceedings of the National Academy of Sciences, 2026)
Rapid growth of wind energy plays a key role in global efforts to reduce carbon emissions, yet public concerns persist about its potential health effects, particularly through noise exposure. While some studies and media reports suggest that wind turbines may contribute to sleep disturbances, anxiety, and even suicide, existing evidence remains limited and inconclusive. This study combines geolocated data on turbines from the US Wind Turbine Database with longitudinal survey data on over 120,000 households (2011–2023) and consumer purchasing records to assess whether proximity to wind turbines affects mental and physical health. We examine a wide range of outcomes, including depression, anxiety, sleep disorders, headaches, and use of sleep aids and painkillers. Comparing households before and after nearby turbine installations, we find no detectable adverse health effects from turbine exposure at typical exposure distances. While we cannot rule out small effects, our CIs exclude moderate-to-large impacts, suggesting that fears about substantial health impacts are not borne out in population-level data. Other disamenities such as noise, shadow flicker, and visual intrusion may still affect quality of life even absent measurable health impacts.